Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations BE BEAUTIFUL! Every girl wants to be beautiful! And why not? Beauty indicates health and happiness, so that the beautiful woman is a blessing to herself and to all who come into contact with her. Personal appearance has a good deal to do with success in life. Perhaps you ask, "How can I, plain Jane, be beautiful?" Every one of us has at least one good point — lovely hair or fine eyes, good teeth or a graceful body, or just a pretty mouth! Even if you are downright plain (though I don't believe it!) you may yet have the charm of an attractive manner and a clear skin. First of all comes super-cleanliness — you cannot have a good complexion if you are not quite clean all over, even where dirt does not show! The skin is all in one piece, you know, and it does not reserve its blotches and pimples for the places where they do not show. Lots of girls spend their pocket money (and lunch money, too) on powders and lip-sticks and creams, but cleanliness will alone work miracles on a muddy complexion. A piece of good toilet soap, a piece of sweet and clean towelling (it should be boiled every week) and plenty of clean water are all that is required to keep an otherwise good skin beautiful. Beauty was never meant to be a luxury, but one of the adjuncts of health. 177/5/8/4